Health devolution in the Philippines: Lessons and insights - Janet S. Cuenca (Philippine Institute for Development Studies (PIDS), 2018)
The study attempts to document the Philippine's experience in health devolution with focus on the Department of Health's efforts to make it work. It also aims to draw lessons and insights that are critical in assessing the country's decentralization policies and also, in informing future policymaking. In particular, it highlights the importance of (i) a well-planned and well-designed government policy to minimize, if not avert, unintended consequences; and (ii) mainstreaming of health policy reforms to ensure sustainability. It suggests the need to (i) take a closer look at the experience of local government units (LGUs) that were able to reap the benefits of health devolution and find out how the good practices can be replicated in other LGUs; and (ii) review and assess the various health reforms and mechanisms that have been in place to draw lessons and insights that are useful for crafting future health policies.
Keywords: 330; Health devolution; health decentralization; devolution; decentralization; health policies